The Urgency of Harmonizing Competition Laws in Moving Towards the ASEAN Free Trade Area - Hanif Nur Widhiyanti (Universitas Lampung, 2020)
ASEAN had created the ASEAN Regional Guidelines on Competition Policy and Handbook on Competition Policy and Law in ASEAN for Business as guides for assessment of the behaviour of business people in the industry and market. The Regional Guidelines “only” help member countries in increasing awareness of the importance of business competition policies. The execution of business competition is then left to the ASEAN member country, to be in accordance with national business competition policies. Meanwhile, the ASEAN Economic Community will allow business people in ASEAN countries to conduct business transactions in whichever country they prefer. Without clear regulations, businesspeople can freely carry out cross-border transactions that can disrupt the domestic market of each ASEAN member country. Differences in regulatory substances and the absence of competition law regulations in several ASEAN member countries will undoubtedly become a challenge for the application of competition laws by businesspeople in the ASEAN regional market. However, in relation to AFTA, the primary urgency is instead the realization of imposing tariffs of 0-5% by performing the harmonization of regulations in the field of Customs and the removal of other forms of Non-Tariff Barriers (NTBs). The removal of trade barriers is one of the things that are also regulated in competition law. This article is the result of normative juridical research that analyzes the differences in the substance of competition law in several ASEAN countries along with their juridical implications, to be able to evaluate the urgency of harmonizing legal regulations on business competition among the member countries of ASEAN.